2019
DOI: 10.2196/12633
|View full text |Cite
|
Sign up to set email alerts
|

Information and Communications Technology as a Health Promotion Method for Older Adults in Assisted-Living Facilities: Three-Arm Group-Randomized Trial

Abstract: Background The application of technology is an important and growing aspect in the field of long-term care. Growing evidence shows the positive impact of technology aids in helping the lives of the elderly. However, it is not known which aspects of information and communications technology (ICT) are preferred by older adults living in long-term care facilities. Objective The goal of the research was to compare the impact of ICT-communication, ICT-entertainment, and conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 26 publications
(28 reference statements)
1
27
0
Order By: Relevance
“…Although not designed as a part of the intervention, participants who received weekly phone calls [ 43 ] also reported shared interests as a way to break the ice as well as to establish a “meaningful reciprocal relationship” and mentioned the importance of knowing about others' lives and events and wanting to talk about ordinary, everyday topics. Pictures as prompt for conversation was also common, retrieving relatives' pictures from social media [ 36 ], using pictures during videochats [ 44 ], or enabling sharing with family and friends [ 33 , 48 , 49 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although not designed as a part of the intervention, participants who received weekly phone calls [ 43 ] also reported shared interests as a way to break the ice as well as to establish a “meaningful reciprocal relationship” and mentioned the importance of knowing about others' lives and events and wanting to talk about ordinary, everyday topics. Pictures as prompt for conversation was also common, retrieving relatives' pictures from social media [ 36 ], using pictures during videochats [ 44 ], or enabling sharing with family and friends [ 33 , 48 , 49 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tablet users reported feeling silly talking to a virtual pet, problems with audio, and delay in messages [ 40 ]. A number of studies also reported that reduced dexterity could lead to difficulties with texting and typing [ 33 ], with gestures such as tapping and swiping [ 48 , 52 ], and coordination issues such as requiring to hold voice icon to record audio messages [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations